(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2024)
The first documented practice of systematic human dissection was performed by the Greek physician Herophilus in the 3rd century B.C. in Alexandria, then the capital of Ptolemaic Egypt. This paper explores the unique circumstances that enabled Herophilus to perform his dissections and the influences that led to the complete cessation of the practice immediately after his death. For additional context, listen to the author’s reflection on the piece below.